2018
DOI: 10.1371/journal.pone.0190785
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia, chronic inflammation, and subclinical atherosclerosis in children and adolescents infected with HIV: The PositHIVe Health Study

Abstract: HIV-infected children and adolescents may be at risk for cardiovascular disease due to chronic inflammation and exacerbation of risk factors. The aim of this study was as follows: 1) compare cardiovascular risk factors, chronic inflammation, and carotid intima-media thickness (IMTc) between the HIV and control groups; 2) determine the association of HIV and antiretroviral (ART) regimens with cardiovascular risk factors, chronic inflammation, and IMTc; and 3) identify variables associated with elevated IMTc. Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…17,18 Of note, metabolic/endocrine events dominated treatmentrelated morbidities in our PHIVA cohort, representing about half of all reported treatment-related events. This is consistent with the established concerns regarding the metabolic effects of ART in children and adolescents, 9,11,19 and are an important consideration when designing optimal long-term ART regimens, particularly given the increased risk of cardiovascular disease for adults living with HIV. 20,21 The younger adolescent age group had a significantly higher rate of overall morbidity compared to their older counterparts, which is mainly attributable to higher disease-related morbidity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…17,18 Of note, metabolic/endocrine events dominated treatmentrelated morbidities in our PHIVA cohort, representing about half of all reported treatment-related events. This is consistent with the established concerns regarding the metabolic effects of ART in children and adolescents, 9,11,19 and are an important consideration when designing optimal long-term ART regimens, particularly given the increased risk of cardiovascular disease for adults living with HIV. 20,21 The younger adolescent age group had a significantly higher rate of overall morbidity compared to their older counterparts, which is mainly attributable to higher disease-related morbidity.…”
Section: Discussionsupporting
confidence: 81%
“…8 There have been particular concerns regarding the metabolic impact of long-term ART, initially around lipodystrophy associated with earlier ART agents to dyslipidemia and insulin resistance 9,10 associated with protease inhibitors (PIs) and their impact on long-term cardiovascular health. 11 Much of the morbidity data to date from low-and middle-income country (LMIC) settings have been presented for broader pediatric populations, with limited data exclusively relating to PHIVA. 1,2 There remains a need for more comprehensive data regarding long-term clinical complications PHIVA face, 12,13 to assist HIV health care providers to prevent, monitor, and manage them, and optimise models of adolescent HIV care.…”
Section: Introductionmentioning
confidence: 99%
“…We documented that 35.9% of PHIV-youths in our study had high hsCRP, which inferred risk of CVD. This corroborates a Brazilian study which reported a significantly higher CRP than healthy control among PHIV-children, mean age 12.2 years [25]. However, a Spanish study in PHIV-children with a mean age of 14.2 years and a mean duration of 3 years on ART, reported that the mean hsCRP level in those without metabolic disturbances was similar to non HIV controls [26].…”
Section: Plos Onesupporting
confidence: 89%
“…Nowadays, non-AIDS co-morbidities represent one of the major causes of morbidity and mortality in perHIV patients compared with age-matched HCs [132,133]. Indeed, perHIV patients present higher levels of glycemia, tryglicerides, CRP, TNF-α, systolic blood pressure, and carotid intima-media thickness compared with age-matched HCs, making them a group at higher risk of developing premature atherosclerosis, CVDs, and MetS [134].…”
Section: Effects Of Hiv and Art Exposure On Inflammation Immunodymentioning
confidence: 99%